2022
DOI: 10.1186/s12890-021-01817-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile and risk factors for bleeding in transbronchial cryobiopsy using a two-scope technique for peripheral pulmonary lesions

Abstract: Background A balloon occlusion technique is suggested for use in cryobiopsy for interstitial lung diseases because of the bleeding risk. However, it may interfere with selection of the involved bronchus for peripheral pulmonary lesions (PPLs). A two-scope technique, in which two scopes are prepared and hemostasis is started using the second scope immediately after cryobiopsy, has also been reported. This study aimed to evaluate the safety and diagnostic utility of transbronchial cryobiopsy usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…The major complications of cryobiopsy are bleeding and pneumothorax [ 31 ]. Prophylactic balloon occlusion and two-scope techniques have been developed to prevent severe bleeding [ 11 , 20 , 22 , 32 ]. Previous studies reported that moderate and severe bleeding occurred in 14.0–38.9% and 0–1.2% of cases, respectively, and the incidence of pneumothorax was 0.8–6.6% when cryobiopsy was performed for PPLs [ 7 , 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The major complications of cryobiopsy are bleeding and pneumothorax [ 31 ]. Prophylactic balloon occlusion and two-scope techniques have been developed to prevent severe bleeding [ 11 , 20 , 22 , 32 ]. Previous studies reported that moderate and severe bleeding occurred in 14.0–38.9% and 0–1.2% of cases, respectively, and the incidence of pneumothorax was 0.8–6.6% when cryobiopsy was performed for PPLs [ 7 , 9 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic balloon occlusion and two-scope techniques have been developed to prevent severe bleeding [ 11 , 20 , 22 , 32 ]. Previous studies reported that moderate and severe bleeding occurred in 14.0–38.9% and 0–1.2% of cases, respectively, and the incidence of pneumothorax was 0.8–6.6% when cryobiopsy was performed for PPLs [ 7 , 9 , 11 , 12 ]. A high number of cryobiopsies has been reported to be unrelated to the severity of bleeding [ 33 ]; however, bleeding obstructs the visual field during bronchoscopy and reduces the approachability of the target bronchus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other techniques such as 2-scope technique for transbronchial cryobiopsies have been employed to minimize bleeding-related complications and achieve hemostasis. 24 , 25 This involves rapidly changing the scopes with 2 operators doing the procedure. However, this still involves a time delay between changing the scopes, involves 2 operators skilled in bronchoscopy, and does not enable real-time visualization during the procedure.…”
Section: Discussionmentioning
confidence: 99%